(untitled) (Indian Journal of Animal Production and Management, 2014)
The study was carried out in Jhunjhunu district of Rajasthan to find out the various constraints perceived by the crossbred cattle keepers in adoption of recommended management practices and possible solutions to overcome the intensity of constraints. The results of the study depicted that distant location and poor services at A.I. centres (1.55 MS), anoestrus and repeat breeding (1.52 MS), poor conception rate of A.I. (1.35 MS) and costly treatment of breeding related problems (1.18 MS) were the major constraints in adoption of breeding management practices. The overall breeding management practices mean score was 1.10. High cost of fodder and concentrate (1.61 MS), non-availability of balance concentrate and mineral mixture (1.44 MS), inadequate irrigation and small land holding for green fodder production (1.30 MS) and lack of extra green fodder for hay and silage preparation (1.28 MS) were the main constraints in feeding management practices. The overall feeding management practices mean score was 1.13. High cost of veterinary medicines (1.46MS), non-availability of veterinary doctor at posting place (1.44MS), distant location of veterinary hospitals (1.12MS) and low awareness about deworming practices (1.10MS) were the major constraints. Constraints regarding overall health care management practices had mean score 1.06. To overcome the constraints, strengthening of A.I. centres, Gopal Yojna, castration of scrub male calf, availability of mineral mixture, green fodder production, pasture land development, increase the number of veterinary hospitals and strengthening of district veterinary mobile unit should be promoted.